ANALISIS PENETAPAN HARGA JUAL MENGGUNAKAN COST PLUS PRICING PADA CV. MIKITA COOKIES JAKARTA - Dwiyatmoko Puji Widodo (Universitas Bina Sarana Informatika, 2014)
The development of today's economy requires every business to be able to improve its competitiveness and expand market share. For that every company should be able to determine the selling price produksnya appropriately in accordance with the price of other similar products on the market. Method of setting the selling price is very varied, one of which is by using the method of Cost Plus Pricing. Cost Plus pricing method is a method of setting the selling price based on cost plus a certain increment (Mark Up) have been determined. In general, this analysis also provides information on determining the cost of products and the determination of full costing is based on the Mark Up with the desired return on investment. This study was conducted with the aim: to determine the cost of production with full costing method, determine the required magnitude Mark Up the Return On Investment by desired and determine the magnitude of the selling price set CV. Mikita Cookies to use Cost Plus Pricing. Data obtained by using techniques of documentation and observation. Analysis of the data using the formula for the cost of full costing of products, formula determination by Mark Up with the desired return on investment, and sales pricing formula using the Cost Plus Pricing. CV. Cookies Mikita is a company engaged in the manufacturing of cake. The results of the analysis as follows: (1). Mark Up The percentage in 2012 was 40% and in 2013 by 42%. (2) The amount of the selling price of the product CV. Mikita Cookies for 2012 is Rp.. 85 374 and for 2013 is Rp.. 82 312Keywords: Determination of Selling Price, Cost Plus Pricing, Mark Up, Return On Investment